A Retrospective Analysis of Infectious Bursal Disease Diagnosed at Poultry Unit of Ahmadu Bello University, Nigeria - Mbuko, I.J.; Musa, W.I.; Ibrahim, S.; Sa`idu, L.; Abdu, P.A.; Oladele, S.B.; Kazeem, H.M. (International Journal of Poultry Science, 2010)
A five year retrospective study (2004-2008) of the prevalence of Gumboro disease (infectious bursal disease, IBD) and other poultry disease diagnosed at the poultry unit of the Ahmadu Bello University Veterinary Teaching Hospital (ABUVTH), Zaria, Kaduna Nigeria was conducted. A prevalence of 7.26% (107 cases) was recorded out of 1473 cases of poultry disease. Gumboro disease occurred throughout the year in Zaria with a high incidence during the festival periods (July-September, October-December and January-March). The outbreaks of IBD were observed to be 1.3 times more likely to occur in pre-rainy season (April-June). Improved breeds of chickens were 5.8 times more likely to suffer from IBD than free range local chickens with broilers being 5.7 times more likely to suffer from the disease than other type of birds followed by layers kept together with cockerels. The prevalence of IBD is influenced by age of birds with an increase in the likelihood of IBD occurring within the age range of 3-5 week. Birds at 5 weeks old were at highest risk. Chickens with one vaccination history against IBD were 8.2 times more likely to suffer from the disease compared to non-vaccinated chickens. This study recommends that poultry farmers should be encourage to improve on farm biosecurity and ensure that their birds are vaccinated at least twice, before 3 and 5 weeks of age (at 1 and 3 or 2 and 4 weeks of age).